An intermolecular RNA triplex provides insight into structural determinants for the pseudoknot stimulator of −1 ribosomal frameshifting - Chou, Ming-Yuan (Oxford University Press, 2010)
An efficient −1 programmed ribosomal frameshifting (PRF) signal requires an RNA slippery sequence and a downstream RNA stimulator, and the hairpin-type pseudoknot is the most common stimulator. However, a pseudoknot is not sufficient to promote −1 PRF. hTPK-DU177, a pseudoknot derived from human telomerase RNA, shares structural similarities with several −1 PRF pseudoknots and is used to dissect the roles of distinct structural features in the stimulator of −1 PRF. Structure-based mutagenesis on hTPK-DU177 reveals that the −1 PRF efficiency of this stimulator can be modulated by sequential removal of base–triple interactions surrounding the helical junction. Further analysis of the junction-flanking base triples indicates that specific stem–loop interactions and their relative positions to the helical junction play crucial roles for the −1 PRF activity of this pseudoknot. Intriguingly, a bimolecular pseudoknot approach based on hTPK-DU177 reveals that continuing triplex structure spanning the helical junction, lacking one of the loop-closure features embedded in pseudoknot topology, can stimulate −1 PRF. Therefore, the triplex structure is an essential determinant for the DU177 pseudoknot to stimulate −1 PRF. Furthermore, it suggests that −1 PRF, induced by an in-trans RNA via specific base–triple interactions with messenger RNAs, can be a plausible regulatory function for non-coding RNAs.